2008
DOI: 10.1111/j.1600-0765.2007.01048.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of butyric acid on adhesion molecule expression by human gingival epithelial cells

Abstract: The results of the present study indicate that butyric acid alters the expression of adhesion molecules by Ca9-22 cells. The elucidation of the mechanism of action of butyric acid on the periodontium may help to clarify several aspects of the onset and progression of periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 35 publications
2
28
0
Order By: Relevance
“…Butyric acid disrupts human cell adhesion and contributes to tissue damage in periodontal disease caused by Gram-negative anaerobes (9,15). This suggests that butyric acid in periodontal pockets disrupts the tight attachment of epithelial cells, resulting in bacterial penetration and periodontal tissue destruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Butyric acid disrupts human cell adhesion and contributes to tissue damage in periodontal disease caused by Gram-negative anaerobes (9,15). This suggests that butyric acid in periodontal pockets disrupts the tight attachment of epithelial cells, resulting in bacterial penetration and periodontal tissue destruction.…”
Section: Discussionmentioning
confidence: 99%
“…High concentrations of butyric acid have been found in the dental plaque of periodontitis patients (10)(11)(12)(13)(14). Takigawa et al demonstrated that butyric acid significantly decreased viability of epithelial cells in a dose-dependent manner and induced ICAM-1 expression (15). Therefore, we postulate that the inhibition of the action of butyric acid on the epithelium reduces the pathogenicity of Gram-negative anaerobes.…”
Section: Introductionmentioning
confidence: 94%
“…Taken together, it seems that butyrate and other SCFA are virulence factors in periodontal disease.Butyrate can activate the free fatty acid receptor-2 (FFAR2), also known as G-protein coupled receptor-43 (GPR43) [20], but also inhibit the histone deacetylase (HDAC) [21]. Using either of these mechanisms, butyrate reduces proliferation and induces apoptosis in gingival fibroblast [22][23][24][25], stimulates T-cell apoptosis [26] and osteoblast maturation [27], as well as pro-inflammatory cytokine release by neutrophils [28]. Butyrate also reduced integrin expression in Ca9-22 epithelial cells [23,29] and promoted autophagy [30].…”
mentioning
confidence: 99%
“…Using either of these mechanisms, butyrate reduces proliferation and induces apoptosis in gingival fibroblast [22][23][24][25], stimulates T-cell apoptosis [26] and osteoblast maturation [27], as well as pro-inflammatory cytokine release by neutrophils [28]. Butyrate also reduced integrin expression in Ca9-22 epithelial cells [23,29] and promoted autophagy [30]. The presence of SCFA in the infectious site attenuates the neutrophils response to A. actinomycetemcomitans as a result of the inhibition of specific isoforms of HDACs, namely, HDAC 1 and 3, but not activation of FFAR2 [31].…”
mentioning
confidence: 99%
“…gingivalis can secrete butyric acid, which affects adhesion molecules in gingival epithelial cells (23). Lipopolysaccharide (LPS), a well-known virulent factor, stimulates proinflammatory cytokines, osteoclast, and bone, resulting in oral diseases (24).…”
Section: Introductionmentioning
confidence: 99%